Pharmacokinetics and distribution of schisandrol A and its major metabolites in rats. (4th March 2019) - Liu, Xu; Cong, Lixin; Wang, Chunmei; Li, He; Zhang, Chengyi; Guan, Xingang; Liu, Peng; Xie, Yu; Chen, Jianguang; Sun, Jinghui
Abstract: 1. Schizandrol A is an active component in schisandra, also the representative component for the identification of schisandra . 2. A rapid resolution liquid chromatography coupled with quadruple–time–of–flight mass spectrometry (RRLC–QTOF/MS) was developed to investigate the pharmacokinetics of schizandrol A after its intragastric administration (50 mg/kg) in rats. 3. Schizandrol A was rapidly absorbed ( T max = 2.07 h), with a longer duration ( t 1/2 = 9.48 h) and larger apparent volume of distribution (Vz/F = 111.81 l/kg) in rats. Schizandrol A can be detected in main organs and the order of its distribution was in the liver > kidney > heart > spleen > brain, particularly higher in the liver. 4. Five schizandrol A metabolites were identified, including 2–demethyl–8(R)–hydroxyl–schizandrin, 3–demethyl–8(R)–hydroxyl–schizandrin, hydroxyl–schizandrin, demethoxy–schizandrin, 2, 3–demethyl–8(R)–hydroxyl–schizandrin, indicating that the hydroxylation and demethylation may be the major metabolic way of schizandrol A. 5. This study defined the pharmacokinetic characteristics of schizandrol A in vivo, and the RRLC–QTOF/MS is more sensitive and less limited by conditions, and needs less samples, which may be a useful resource for the further research and development of schisandrol A.